Importance of Rubber Characteristics in the Frictional Response of Asphalt Concrete Surfaces. Issue 1 (January 2015) - Villani, Mirella M.; Scarpas, Athanasios; de Bondt, Arian; Khedoe, Radjan; Kasbergen, Cor
During rubber–asphalt concrete (AC) interaction, the indentation of the elastomer by the AC asperities causes its deformation and hence dissipation of internal energy. The amount of expended energy is related primarily to surface roughness, thermomechanical response of the rubber, speed, temperature, and applied pressure. Friction can be evaluated on the basis of the amount of expended energy. Because of the many factors involved and their interrelation, laboratory or in situ measured friction is only an indicative value heavily dependent on the specific set of testing conditions. Some conditions, such as rubber characteristics or temperature, are difficult to control, and their influence on friction is difficult to quantify. This research examined the interaction between two rubber types (with characteristics similar to those used for in situ testing) and three typical AC mixes (AC10, stone mix asphalt, and porous asphalt). The AC surface characteristics were studied with a laser scanner and the viscoelastic properties of the rubber with dynamic shear rheometer tests, and the interaction between the two materials was investigated with a purpose-developed and purpose-built skid-resistance interface testing device. The laboratory results were further elaborated with a newly developed computational tool, M2D. Through a detailed laboratory study followed by computational analyses, this research demonstrates the importance of accounting for rubber characteristics during friction evaluation and demonstrates how the characteristics of the rubber can be taken into account in friction prediction tools.